EDUKASI PENCEGAHAN DAN PENGENDALIAN COVID-19 DI DESA JLOBONG RT 06 RW 01 PUSPORENGGO, MUSUK, BOYOLALI - OCTAVIA VICKY AYU PERMATASARI; UNNA RIA SAFITRI; DONNA SETIAWATI (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
Coronavirus Disease 19 (Covid-19) is a new type of disease that attacks the human respiratory system and has been declared by WHO as a Covid-19 pandemic. In Indonesia, in order to prevent the transmission of this virus, various efforts have been made, namely using masks when in public places, lockdowns in red zones, and physical quarantine. In an effort to help prevent the virus, regions in Indonesia have also implemented various policies. As has been done in Jlobong Rt 06/ Rw 01 Pusporenggo, Musuk, Boyolali. Participants in Real Work Lectures in an effort to educate understanding several programs aimed at preventing the transmission of Covid-19 and helping the economy of the people affected by Covid-19, including ordering a team of Covid-19 volunteers in Jlobong Village, distributing aid, as well as education and socialization. the use of masks to the people of Jlobong Village.